Hydrodynamic Simulations of Circumstellar Envelopes under the Gravitational Influence of a Wide Binary Companion: Comparison Between Circular and Elliptical Orbits - Hung, Tran Ngoc; Dinh, Trung Van; Bao, Nguyen Thi Thanh; Hai, Bui Van; Bang, Pham Dong (Communications in Physics, 2019)
Shapes of circumstellar envelopes around mass losing stars contain information of the very inner region of the envelope where mass loss process takes place. It’s well known that the presence of a binary companion leads to strong influence on the structure of the envelope through orbital motion of the mass losing star and the gravitational interaction of the companion with the stellar wind. To investigate this effect and structures of envelopes, we have performed high resolution hydrodynamic simulations of a wide binary system in a number of orbital configurations. Our simulations clearly show the importance of the equation of state of the gas because in isothermal case the width of the spiral arm is significantly broadened with respect to the ideal gas case, therefore resulting in unrealistic spiral patterns. As the orbital geometry changes from circular to elliptical, our simulation results show that the spiral becomes bifurcated and increasingly asymmetric as indicated in previously published results. In the polar direction, the prominent alternating arcs associated with circular orbital configuration morph into almost continuous circular rings. The physical condition of the gas in the envelope is shown to vary strongly between the spiral arm and inter-arm regions. Our hydrodynamic simulations will be useful to interpret high angular resolution observations of circumstellar envelopes.